A historical perspective on malaria control in Brazil - Griffing, Sean Michael (Mem Inst Oswaldo Cruz, 2015)
Malaria has always been an important public health problem in Brazil. The early history of Brazilian malaria and its control was powered by colonisation by Europeans and the forced relocation of Africans as slaves. Internal migration brought malaria to many regions in Brazil where, given suitableAnopheles mosquito vectors, it thrived. Almost from the start, officials recognised the problem malaria presented to economic development, but early control efforts were hampered by still developing public health control and ignorance of the underlying biology and ecology of malaria. Multiple regional and national malaria control efforts have been attempted with varying success. At present, the Amazon Basin accounts for 99% of Brazil’s reported malaria cases with regional increases in incidence often associated with large scale public works or migration. Here, we provide an exhaustive summary of primary literature in English, Spanish and Portuguese regarding Brazilian malaria control. Our goal was not to interpret the history of Brazilian malaria control from a particular political or theoretical perspective, but rather to provide a straightforward, chronological narrative of the events that have transpired in Brazil over the past 200 years and identify common themes.